Investigation of Nanofluids Selection for Solar Thermal Collectors - Zulkafli, Muhammad Harith (IRC, 2016)
Solar thermal collectors are gaining popularity across the world as green alternatives for domestic water heating. Using nanofluid as collector’s heating fluid has proven to increase solar collector’s energetic efficiency. The problem faced is what is the most important nanofluid parameter that should be considered for a flat plate solar collector? The main objective of the project is to define the most significant parameters for nanofluid selection. Scope of project covers 9 factor parameters namely volume fraction (φ), temperature, solar irradiation (